Sodium Chloride in the Germination and Initial Growth of Three Huauzontle (Chenopodium berlandieri subsp. nuttalliae) Cultivars (Agro Productividad, 2025)
Objective: To determine the effect of sodium chloride (NaCl) and cultivar on germination and initial growth of huauzontle (Chenopodium berlandieri subsp. nuttalliae).Design/methodology/approach: A 3 × 5 factorial experiment in a completely randomized design was conducted. Three huauzontle cultivars (Mexico City, Puebla, and Tlaxcala) and five doses of NaCl (0, 75, 150, 225, and 300 mM) were evaluated. Each treatment had five replicates. The germination percentage was evaluated 24 h after sowing, plant height of the seedlings for 11 d, and the weights of fresh and dry biomass were determined at 11 d after germination. The data were analyzed using ANOVA, Tukey’s test (p ≤ 0.05), and a regression model was generated for the variable seedling height as a function of the time of exposure to NaCl.Results: Seed germination began 24 h after sowing in the three cultivars at all NaCl concentrations evaluated. The germination percentage was reduced by 17.6% at 300 mM compared to the control without salinity. Seedling height was higher in the Mexico City and Tlaxcala cultivars at 75 and 150 mM compared to the control; in these treatments, growth was only inhibited with 300 mM NaCl. On the contrary, the Puebla cultivar showed a reduction in growth starting at 225 mM NaCl. The weights of fresh and dry biomass were only affected by the cultivar study factor, where Mexico City followed by Puebla had the highest means; both higher than Tlaxcala.Limitations of the study/implications: This study only considers the germination and initial growth phases in the three huauzontle cultivars. Therefore, it is necessary to evaluate the effects of salinity in later phenological stages.Findings/conclusions: The responses observed in huauzontle in germination and initial growth depend on the NaCl concentration and the cultivar. The germination percentage decreased only with the 300 mM NaCl dose with respect to the control. NaCl at doses of 75 and 150 mM NaCl promoted growth in the Mexico City and Tlaxcala cultivars. The Mexico City cultivar had the highest fresh and dry biomass weights, followed by Puebla and Tlaxcala.